Estimating the Welfare Costs of Reforming the Iraq Public Distribution System : A Mixed Demand Approach - Krishnan, Nandini; Olivieri, Sergio; Ramadan, Racha (Taylor and Francis, 2020)
Through three decades of conflict, food rations delivered through the public distribution system (PDS) have remained the largest safety net among Iraq’s population. Reforming the PDS continues to be politically challenging, notwithstanding the system’s import dependence, economic distortions, and unsustainable fiscal burden. The oil price decline of mid-2014 and recent efforts to rebuild and recover have put PDS reform back on the agenda. The government needs to find an effective way to deliver broad benefits from a narrow economic base reliant on oil. The study described here adopts a mixed demand approach to analyzing household consumption patterns for the purpose of assessing plausible reform scenarios and estimating the direction and scale of the associated welfare costs and transfers. It finds that household consumption of PDS items is relatively inelastic to changes in price, particularly among the poor. The results suggest that any one-shot reform will have sizeable adverse welfare impacts and will need to be preceded by a well-targeted compensation mechanism. To keep welfare constant, subsidy removal in urban areas, for example, would require the poorest and richest households to be compensated for, respectively, 74 per cent and nearly 40 per cent of their PDS expenditures.